The Role of Optic Nerve Sheath Diameter in Differential Diagnosis in Patients with Headache, A Prospective, Randomized Controlled Study - Ayşegül İşlek Yüksel; Fatih Selvi; Serkan Yüksel; Mustafa Avcı; Gülsüm Çalışkan Günay; Nalan Kozacı (Global Emergency and Critical Care)
Objective: This study aimed to evaluate the usability of the optic nerve sheath diameter (ONSD) in the differential diagnosis of headache. Materials and Methods: This study included non-traumatic patients with headache. Patients were divided into three groups. Primary headache was assigned to group 1, secondary headache to group 2, and healthy volunteers to group 3. ONSD was measured by ultrasonography before computed cranial tomography imaging. Results: A total of 50 patients in groups 1 and 2 and 50 healthy volunteers in group 3 were included. The mean ONSD of healthy volunteers was 4.2 mm, and the mean ONSD difference between eyes was 0.2 mm. The mean ONSD for the primary headache was 4.5 mm, and the mean ONSD difference for both eyes was 0.2 mm. The ONSD of the secondary headache was measured as 6.2 mm, and the ONSD difference between the eyes was 0.3 mm. The ONSD difference in both eyes and the ONSD of patients with secondary headache were higher than those in groups 1 and 3 (p<0.001). The ONSD cutoff value, which was positive on CT imaging, was 5.2 mm. Conclusion: The ONSD and difference in ONSD can be used in the differential diagnosis of primary and secondary headache.